Synthesis and Spectroscopic study of Pd(II)- Salicylaldoxime complexes with amine ligands - Emad N. Al_Sabawi; Ahmed S. Al-Janabi; Hayfa Muhammed Jerjes (Tikrit Journal of Pure Science, 2021)
New Pd(II) complexes  of Salicylaldoxime (HSaly) with amine ligands {amine = Bipy, Phen and en} were synthesized and characterized by using CHN analysis, FT-IR spectra, molar conductivity and 1H NMR spectra. The HSaly ligand was coordinated with the Pd(II) ion as bidentate chelating ligand in complex [Pd(Saly)2], through oxygen atom of hydroxylate group and nitrogen atom of oxime group. However, it was bonded as monodentate ligand in complexes [Pd(Saly)2(amine)] (2-4) via the oxygen atom of hydroxylate group. The amines were coordinated as bidentate chelate via N atom to give a square planner around the Palladium (II).